(untitled) (Academicia Globe: Inderscience Research, 2021)
Feeding ostriches on many farms creates problems because they have not been previously studied in the country. Therefore, this article discusses the skills of keeping and feeding ostriches in order to increase their productivity and achieve high economic efficiency.